An evaluation of a breastfeeding peer support service in North East England: A qualitative study with service users, practitioners and volunteers - Kerry Brennan-Tovey; Simon Barrett; Louise Hayes; Malcolm Moffat; Gina Nguyen; Maria Raisa Jessica (Ryc) Aquino; Judith Rankin (PLoS ONE, 2026)
Background Breastfeeding has health benefits for women and infants. Although the WHO recommends that infants are breastfed exclusively for the first six months, exclusive breastfeeding rates remain low in the UK, with many women stopping breastfeeding within six weeks of their infant’s birth. Many women face challenges initiating and continuing breastfeeding, including low confidence, limited support and misinformation. Breastfeeding peer support (BPS) services play a vital role in supporting women to continue to breastfeed by connecting new mothers with trained volunteers who offer advice, emotional encouragement and reliable information. Methods This study aimed to undertake a formative evaluation of the BPS service in Newcastle upon Tyne from the perspective of those who deliver the services, the wider healthcare team and mothers’ experiences of utilising the service. This evaluation used a qualitative design, consisting of one-to-one semi-structured interviews with practitioners, volunteers, healthcare professionals and service users. Recruitment took place between 28 th March – 14 th May 2025. Recorded interview data were transcribed verbatim and analysed using Braun and Clarke’s coding reliability thematic analysis. Results Twenty-two interviews were conducted (n = 11 practitioners, volunteers and healthcare professionals and n = 11 service users). Analysis identified four themes: mechanisms of the service; support offered by the service; outcomes of the service, and challenges to service delivery. Overall, the BPS was considered a supportive service by participants. Conclusions The normalisation of breastfeeding was seen as crucial to the service, while service users described that the emotional support provided helped to increase their confidence in breastfeeding. Challenges were identified for the service, including engaging those aged under 25 years and those for whom English is a second language. These findings will be used to inform the future development of the service.